The impact of screen exposure on early literacy skills of preschool children: the mediation of parental media intervention - Zu, Jing; Zhang, Yixuan; Wang, Ruifang (Frontiers in Psychology, 2026)
IntroductionThis study investigates the impact and mechanisms of screen media use on early language development in preschoolers.MethodsVia questionnaires with 516 parents of 3-6-year-olds in China, we examined children’s screen exposure and early literacy levels, then constructed a model to explore parental media intervention as a mediator.ResultsResults showed: entertainment-based screen activities significantly negatively predicted early literacy, while educational use had a weak positive correlation; entertainment activities indirectly affected literacy through parental intervention, with mediating effects ranked as restrictive > educational active > caretaking active intervention.DiscussionFindings reveal how technology and family microsystems influence early literacy, offering tailored guidance for parents on screen use.